Demographic divide and labor migration in the Euro-Mediterranean region - Mehmet S. Tosun (Institute for the Study of Labor (IZA), 2011)
This paper provides a demographic outlook of the Euro-Mediterranean region and then shows the economic and fiscal consequences of such demographic differences within a two-region model with international labor mobility. International labor mobility is also examined through an externalities framework where brain drain from migration could be taxed by the home countries. Taxing the brain drain has a substantial limiting effect on labor migration and a small negative effect on per worker growth. On the other hand, it could be a solution to the negative externality problem associated with brain drain. It is also found that such tax can raise substantial tax revenue for the SMCs which could be used to enhance human capital in the region.
urn:nbn:de:101:1-201201103708
Keywords: E62; F22; H23; H24; H41; 330; demographic divide; demographic deficit; population aging; youth bulge; labor mobility; brain drain; overlapping generations; endogenous tax policy; Mediterranean region; Internationale Arbeitsmobilität; Brain Drain; Steuer; Bevölkerungsökonomie; Zwei-Länder-Modell; Mittelmeerraum; Alternde Bevölkerung; Europa